Increasing Firm Value via Conservatism in Accounting - Moh. Ubaidillah (Master of Accounting Universitas Trunojoyo Madura, 2021)
This study aims to determine the effect of firm size and profitability on firm value with accounting conservatism as a moderating variable. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 as many as 183 companies. The sampling technique used purposive sampling which resulted in 72 manufacturing companies. The data analysis technique uses regression analysis with SPSS 24. The results of this study indicate that firm size and profitability have a positive and significant effect on firm value. Furthermore, the variable of accounting conservatism is able to moderate the effect of firm size and profitability on firm value in a positive and significant way.